The Impact of Digital Collaboration, Government Support, And Technology Access on Entrepreneurship Interest Among Generation Z in Sumbawa Regency - Henriawan; Rian Hardiansyah (Al-Qalam Institue, 2026)
This study aims to examine the impact of digital collaboration, government support, and technology access on entrepreneurial interest among Generation Z in Sumbawa Regency. A quantitative approach was adopted, employing surveys and Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis using SmartPLS 3.2.9. Primary data were collected from 100 Generation Z respondents (born 1997–2012) through an online Likert-scale questionnaire using purposive sampling. Measurement model evaluation confirmed convergent and discriminant validity, along with high instrument reliability. Structural model analysis revealed that technology access, digital collaboration, and government support significantly influenced entrepreneurial interest, with technology access being the most dominant predictor. These results highlight the importance of digital infrastructure in addressing geographical disparities, enhancing social influence via online networks, and reducing perceived risks through supportive policies. Practically, the findings provide guidance for stakeholders to modernize digital entrepreneurship programs, expand ICT infrastructure, and improve the dissemination of online policy initiatives. The study contributes theoretically by integrating the Theory of Planned Behavior with Social Cognitive Theory and the Technology Acceptance Model in a rural context. Limitations of the cross-sectional design suggest the need for longitudinal research to examine the dynamics of sustainable entrepreneurial behavior.